A longitudinal study of early reading development in two languages: comparing literacy outcomes in Irish immersion, English medium and Gaeltacht schools. Issue 5 (2nd September 2016) - Parsons, Christine E.; Lyddy, Fiona
Abstract : Schools in Ireland vary in how they introduce reading in the two official languages, Irish and English. There is particular variability within immersion (Irish medium) schools. Some introduce Irish reading first (IRF) and others English reading first (ERF). This study compared the development of Irish and English skills in children attending different school types, assessing word reading, decoding and vocabulary at three time points (second, third and fourth year of schooling). Children attending Irish-medium schools and a school in an Irish-speaking (Gaeltacht) community performed significantly better than children attending an English-medium school on the Irish tasks. Differences between the IRF and ERF school children were evident only at the first time point, with IRF children showing an early advantage in decoding. Differences between the school groups on the English tasks were largely resolved by the fourth year of schooling. Comparing the Irish-medium groups on English reading, the Gaeltacht group initially lagged behind the others, but there was no difference by the fourth year of schooling. These findings suggest that the language in which reading is formally introduced is not critical to later reading attainment. Furthermore, teaching through Irish was associated with Irish language advantages, without detriment to English reading skill as measured here.